2011
DOI: 10.1590/s1809-48722011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos pacientes do programa de saúde auditiva do estado de Santa Catarina atendidos no HU-UFSC

Abstract: Introduction:Hearing is one of the essential functions for the development of language and its deficiency may lead to several consequences. Objective:To describe the profile of patients of the Hearing Health Program of the State of Santa Catarina attended at the College Hospital of the Federal University of Santa Catarina. Method:We performed a retrospective study with the patients with hearing aid indication attended in the years 2007 and 2008. They were divided into 2 groups: children (< 18 years) and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 7 publications
(15 reference statements)
2
5
0
12
Order By: Relevance
“…The complaints of hearing loss, tinnitus and dizziness coincide with results of a national study that evaluated the audiological profile of adults and the elderly in the city of São Paulo 4 . As for comorbidities, hypertension, cholesterol alteration, diabetes and heart problems were observed, which corroborate the results of the study that described the profile of patients seen in the Hearing Health Program at Santa Catarina, where it was observed that 30% of the participants had hypertension, 8.9% diabetes and 3.4% cardiopathies 8 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The complaints of hearing loss, tinnitus and dizziness coincide with results of a national study that evaluated the audiological profile of adults and the elderly in the city of São Paulo 4 . As for comorbidities, hypertension, cholesterol alteration, diabetes and heart problems were observed, which corroborate the results of the study that described the profile of patients seen in the Hearing Health Program at Santa Catarina, where it was observed that 30% of the participants had hypertension, 8.9% diabetes and 3.4% cardiopathies 8 .…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the relative clinical findings, the data corroborate previous studies in terms of the predominance of the sensorineural type [7][8]16 and of the moderate degree [5][6]8,14,16 . The complaints of hearing loss, tinnitus and dizziness coincide with results of a national study that evaluated the audiological profile of adults and the elderly in the city of São Paulo 4 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Sensorineural hearing loss had the greatest prevalence, which was also observed in public hearing health programs in Santa Maria (RS) 15 , Montes Claros 17 , Florianópolis (SC) 22 , Ribeirão Preto (SP) 19 , São Paulo (SP) 18 and a predominance of moderate hearing loss is supported by studies from Monte Negro (RO) 4 , Santa 23 , a study also found that, due to insufficient financial resources, this population was not able to utilize PSAP until the establishment of Hearing Health Care Services.…”
Section: Discussionmentioning
confidence: 85%
“…It is common for neonates to show the association of some RIHL, especially if they stayed in the NICU for more than five days (4) . It is known that multiple risk indicators increase the chance of compromising the auditory system and that the occurrence of hearing loss is higher in the group of children with these indicators (20,21) .…”
Section: Discussionmentioning
confidence: 99%